Empire Without Imperialism: The Habsburg Experience of Europe’s Supranational Unity - Габсбург-Лотрінген, Франц Володимир; Хилько, Микола Іванович (Київський національний університет імені Тараса Шевченка, 2025)
The article offers a comprehensive historical-political and political-philosophical analysis of the Habsburg Empire as a distinctive type of supranational political order that fundamentally differs from classical models of imperialism. The central problem—the possibility of political unity without systemic coercion and violent unification—is addressed through a conceptualization of the Habsburg experience as a form of an “empire without imperialism.”The study substantiates that dynastic continuity and the logic of the longue durée functioned as mechanisms for stabilizing a multinational space, ensuring the continuity of political order without the need for ethnocultural homogenization. It demonstrates that marital diplomacy and the system of dynastic alliances constituted an early model of “soft power,” in which the legitimacy of authority was grounded in integration and compromise rather than conquest.It is argued that the political philosophy of Habsburg universalism rested on an institutionalized tension between the universal and the particular, wherein local autonomies and regional specificities did not negate imperial unity but rather formed its functional foundation. The imperial order is shown to have served as a mechanism for containing interethnic conflicts and political fragmentation, despite imposing limits on radical forms of national self-determination.The article further reveals that Habsburg cosmopolitanism possessed an “embedded” character, combining supranational loyalty with the preservation of local identities and thereby shaping a distinctive Central European model of cultural integration. It is established that the dissolution of the empire in 1918 marked the end of a political form but not the disappearance of its institutional ideas, which persisted in the principles of multilevel governance, legal pluralism, and a politics of compromise.The scholarly contribution of the article lies in rethinking the imperial phenomenon beyond its reduction to violence and domination and in substantiating the Habsburg experience as a theoretical resource for analyzing contemporary integration processes. The study demonstrates that the problem of unity without coercion remains an open political and philosophical challenge of the twenty-first century.

У статті здійснено комплексний історико-політичний та політико-філософський аналіз Габсбурзької імперії як особливого типу наднаціонального політичного порядку, що принципово відрізняється від класичних моделей імперіалізму. Поставлену проблему - можливість політичної єдності без системного примусу та насильницької уніфікації розв’язано шляхом концептуалізації габсбурзького досвіду як форми «імперії без імперіалізму».У ході дослідження обґрунтовано, що династична тяглість і логіка тривалого часу виконували функцію стабілізації багатонаціонального простору, забезпечуючи спадкоємність політичного порядку без необхідності етнокультурної гомогенізації. Показано, що дипломатія шлюбу та система династичних союзів формували ранню модель «м’якої сили», у якій легітимація влади ґрунтувалася на інтеграції та компромісі, а не на завоюванні.Доведено, що політична філософія габсбурзького універсалізму базувалася на інституціоналізованій напрузі між універсальним і партикулярним, де локальні автономії та регіональні специфіки не заперечували імперську єдність, а становили її функціональну основу. Виявлено, що імперський порядок виконував роль механізму стримування міжетнічних конфліктів і політичної фрагментації, навіть попри обмеження радикальних форм національного самовизначення.Розкрито, що габсбурзький космополітизм мав «вкорінений» характер і поєднував наднаціональну лояльність із збереженням локальних ідентичностей, формуючи специфічну центральноєвропейську модель культурної інтеграції. З’ясовано, що розпад імперії у 1918 р. означав кінець політичної форми, але не зникнення її інституційних ідей, які збереглися у вигляді принципів багаторівневого управління, правового плюралізму та політики компромісу.Науковий внесок статті полягає у переосмисленні імперського феномену поза редукцією до насильства та домінування і в обґрунтуванні габсбурзького досвіду як теоретичного ресурсу для аналізу сучасних інтеграційних процесів. Дослідження демонструє, що проблема єдності без примусу залишається відкритою політичною і філософською проблемою ХХІ століття.
Імперія без імперіалізму: габсбурзький досвід наднаціональної єдності Європи
Keywords: Habsburg Empire; supranational unity; empire without imperialism; political universalism; dynastic continuity; multilevel governance; cosmopolitanism; Central Europe; political order; unity without coercion; Габсбурзька імперія; наднаціональна єдність; імперія без імперіалізму; політичний універсалізм; династична тяглість; багаторівневе управління; космополітизм; Центральна Європа; політичний порядок; єдність без примусу